В) 7(х^2 + 2x) = 2(x^2 + 24)
7x^ 2 + 14x = 2x^2 + 48
7x^2 - 2x^2 + 14x - 48 = 0
5x^2 + 14x - 48 = 0
D = 196 - 4(5)(-48) = 196 + 960 =1156; YD = 34
x1 = (-14 + 34) / 10 = 20/10 = 2
x2 = (-14 - 34) / 10 = - 4,8
Ответ: х1 = 2
х2 = - 4,8
------------------------------------------------------------------------------------------
г) 15х^2 + 5x - 8 + 28x = 6x^2 + 34
15x^2 - 6x^2 + 33x - 42 = 0
9x^2 + 33x - 42 = 0 -----> сократим на 3
3x^2 + 11x - 14 = 0
D= 121 -4(3)(-14) = 121 + 168 = 289; YD = 17
x1 = (-11 + 17) / 6 = 1
x2 = (-11 - 17) / 6 = - 4цел.2/3
Ответ: х1 = 1
х2 = - 4цел.2/3